EDUCATION ON THE CONSUMPTION OF FATTY FOODS IN OBESE ADULTS ON CHANGES IN KNOWLEDGE AND EATING PATTERNS - Harti, Leny Budhi (Caring: Jurnal Pengabdian Masyarakat, 2024)
According to the 2014 Individual Food Consumption Survey, 27% of Indonesia's population consumes more fat than dietary recommendations. Consuming fat > 30% of total energy might raise the Body Mass Index (BMI) and increase the risk of being overweight or obese. This activity aimed to provide nutritional education on regulating fatty food consumption in obese people. Counseling 20 obese adults was the focus of the activities. The parameters measured were pre-and post-test scores, fat, and cholesterol intake before and after counseling. The average pre and post-test scores were 57.00 ± 14.90 and 73.00 ± 7.32, respectively (p = 0.04). Before and after counseling, the average fat intake was 101.14 ± 12.82 and 67.43 ± 8.55, respectively (p = 0.00). The average cholesterol intake before and after counseling was 326 ± 51.33 and 227 ± 44.25 (p = 0.00). This activity concluded that education regarding managing fatty foods can influence knowledge, fat, and cholesterol intake